Теплообмен при импульсной подаче диспергированной воды на высокотемпературную поверхность - Переселков, Александр Романович (НТУ "ХПИ", 2011)
The heat transfer whenapplying water dispersed on high temperature surface was investigated. The influence of mean-time irrigating density on specific heat-fluxis presented. It is shown that heat flux is reduced compared with continuous supply of drops.
Keywords: зона орошения; интенсивность охлаждения; мотор-генератор; монтажная пластина